A new family of set-theoretic solutions of the Yang–Baxter equation. Issue 4 (3rd April 2018) - Castelli, M.; Catino, F.; Pinto, G.
ABSTRACT: A new family of non-degenerate involutive set-theoretic solutions of the Yang–Baxter equation is constructed. Two subfamilies, consisting of irretractable square-free solutions, are new counterexamples to Gateva-Ivanova's Strong Conjecture [7 ]. They are in addition to those obtained by Vendramin [15 ] and [1 ].